0
$\begingroup$

Can someone please prove to me that $I = PRT$, where $P$ is the principal, $R$ is the interest rate, and $T$ is the number of years/time. I have seen $I = P(1+TR) = P+PTR$ which does not equal $PRT$, so I am slightly confused. Any help is appreciated, Thanks!

$\endgroup$
  • 1
    $\begingroup$ It should be $\Delta P=PRT$, not $I$. Then: $$I=P+\Delta P=P+PRT=P(1+RT).$$ $\endgroup$ – Tunk-Fey Apr 11 '14 at 15:55
  • $\begingroup$ Well, then either $P=0$ or one of the two things you tell us are wrong. $\endgroup$ – mathse Apr 11 '14 at 15:55
  • 1
    $\begingroup$ Dimensional analysis $\endgroup$ – evil999man Apr 11 '14 at 15:58
  • $\begingroup$ @Awesome you wouldn't be able to distinguish between them with dimensional analysis: $$[M]\cong [M][T]^{-1}[T] + [M] \cong [M][T]^{-1}[T]$$ Where $[M]$ is units of money. $\endgroup$ – Thomas Russell Apr 11 '14 at 15:59
  • $\begingroup$ @Tunk-Fey: Everywhere I see on the internet it says the $I = PRT$, not delta P. $\endgroup$ – OpieDopee Apr 11 '14 at 15:59
1
$\begingroup$

You have for simple interest at a fixed interest rate per time period $R$:

$$I=\sum_{i=1}^{T}PR=PRT$$

Where $I$ is the total interest after $T$ time periods. Therefore your other formula should read:

$$P(T)=P(0)(1+RT)$$

Where $P(T)$ is the principle after $T$ time periods.

| cite | improve this answer | |
$\endgroup$
-1
$\begingroup$

For 100 we get $r$,then for $p$ we get $(pr/100)$,first time, same thing we will get after 2nd year similarly 3rd, therefore

s.i after $t$ time=$(pr/100)+(pr/100)+......................(pr/100)=(prt/100)$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.